2003
DOI: 10.1046/j.1440-1797.2003.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression in chronic haemodialysed patients

Abstract: From April 2000 to April 2001, a total of 108 chronic stable haemodialysed patients (34 males aged 57.76 +/- 12.68 years under haemodialysis treatment for 31.41 +/- 24.71 months and 74 females aged 54.99 +/- 12.87 years under haemodialysis for 41.47 +/- 33.47 months) were studied for signs of clinical depression. Depression was measured by using 'The Taiwanese Depression Questionnaire (TDQ)'. After analysing various possible factors, we chose to study three dimensions: affective change, somatic complaint and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
3
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 21 publications
3
24
3
9
Order By: Relevance
“…Most of patients weren't capable of tolerating work load besides their illness and not because they were aged. This meets the finding of the study conducted by Chen et al, who studied signs of clinical depression of chronic haemodialysis patients in Taiwan [23]. They found that three fourth of the study sample didn't work.…”
Section: Discussionsupporting
confidence: 87%
“…Most of patients weren't capable of tolerating work load besides their illness and not because they were aged. This meets the finding of the study conducted by Chen et al, who studied signs of clinical depression of chronic haemodialysis patients in Taiwan [23]. They found that three fourth of the study sample didn't work.…”
Section: Discussionsupporting
confidence: 87%
“…TDQ scores range from 0 to 54, with higher scores indicating higher levels of depression traits. In previous validation of the TDQ with the Beck Depression Inventory (BDI) and the Hamilton Rating Scale for Depression (HRSD), the sensitivity, specificity and reliability of the TDQ was comparable to those of the BDI and the HRSD [23][24][25] both are internationallyused screening tools for depression in community population; for the TDQ, the optimal cut-off score was set at 19 based on a Receiver Operating Characteristic (ROC) curve analysis 24,26) , and a sensitivity of 0.89 and a specificity of 0.92 was shown based on a cross examination with the Structured Clinical Interview for DSM-III-R Depressive Disorders by psychiatrists 26) . In our study, the Cronbach's alpha coefficient of the TDQ was 0.94, and no significant difference between genders was found.…”
Section: Chinese Version Of Job Content Questionnaire (C-jcq)mentioning
confidence: 99%
“…Podaci o prevalenci depresije i o njenoj ulozi u obolijevanju i preživljavanju bolesnika sa terminalnom bubrežnom insuficijencijom, koji se liječe nekom od metoda dijaliza, su minorni i kontraverzni [6,7]. Ovo je dijelom posljedica korištenja različitih instrumenata za otkrivanje depresije kod ovih bolesnika, kao i sličnosti između simptoma depresije i simptoma uremije [8,9].…”
Section: Uvodunclassified
“…Ovo je dijelom posljedica korištenja različitih instrumenata za otkrivanje depresije kod ovih bolesnika, kao i sličnosti između simptoma depresije i simptoma uremije [8,9]. U prvim radovima o učestalosti depresije kod bolesnika sa terminalnom insuficijencijom bubrega navodi se prevalenca između 0% i 100% [6,7]. Tek su rezultati multicentrične, prospektivne DOPPS (Dialysis Outcomes Practices Patterns Study) studije, koja je obuhvatila 9389 bolesnika na dijalizi u 9 zemalja Evrope i SAD i u kojoj je korišten jedinstveni CES-D instument za skrining depresije, pokazali ujednačenu prevalencu depresije između 40 i 45% [10,11].…”
Section: Uvodunclassified